Hyperpigmentation in skin of colour: Therapeutical benefits of isobutylamido‐thiazolyl‐resorcinol (Thiamidol®), an effective tyrosinase inhibitor, in phototypes IV-VI - Barbara Schuster; Adel Sammain (Wiley, 2024)
Abstract Skin of colour, defined as Fitzpatrick skin types IV-VI, is especially susceptible to hyperpigmentation concerns such as melasma and postinflammatory hyperpigmentation (PIH). Treating hyperpigmentation in skin of colour is challenging due to increased risk of PIH, which can be induced by the treatments. Isobutylamido‐Thiazolyl‐Resorcinol (ITR), a tyrosinase inhibitor, has previously been identified as an effective and safe solution for hyperpigmentation, inhibiting melanin production without common side effects. This review evaluates available evidence on ITR's efficacy and safety for the management of hyperpigmentation in skin types IV-VI. Three publications reporting four studies were reviewed. Two randomised controlled trials assessed the efficacy and tolerability of ITR for the management of melasma in patients with skin of colour, whereas one randomised clinical trial and one observational real‐world study explored therapeutic benefits for patients with acne‐related PIH. A total of 234 participants completed the four reviewed studies, of which 232 were skin of colour. In a randomised vehicle‐controlled trial, ITR significantly improved Melasma Area and Severity Index scores and quality of life over 24 weeks of application compared to baseline and vehicle. A comparative clinical trial showed ITR, alone or with hyaluronic acid, effectively reduced melasma. A randomised vehicle‐controlled study in patients with acne‐related PIH showed ITR significantly reduced PIH visibility as compared to baseline and vehicle. An observational real‐world study confirmed effective PIH reduction by ITR in a real‐life setting. All studies showed good tolerability of the examined ITR‐containing formulations. The results collectively support ITR as a safe and effective cosmetic solution in skin of colour. ITR emerges as a reliable hyperpigmentation management option for this patients groups, backed by robust methodologies. Future research should include more patients with Fitzpatrick skin type VI and explore potential benefits of combining ITR and laser treatments in skin of colour to reduce PIH risk.